2007
DOI: 10.1007/s00792-007-0101-2
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of gene, and activation of an organic solvent-stable lipase from Pseudomonas aeruginosa LST-03

Abstract: Organic solvent-tolerant Pseudomonas aeruginosa LST-03 secretes an organic solvent-stable lipase, LST-03 lipase. The gene of the LST-03 lipase (Lip9) and the gene of the lipase-specific foldase (Lif9) were cloned and expressed in Escherichia coli. In the cloned 2.6 kbps DNA fragment, two open reading frames, Lip9 consisting of 933 nucleotides which encoded 311 amino acids and Lif9 consisting of 1,020 nucleotides which encoded 340 amino acids, were found. The overexpression of the lipase gene (lip9) was achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…To prevent the formation of inclusion bodies, the recombinant cells were cultured at a low temperature (20°C) after the addition of IPTG, for a higher temperature (e.g., 37°C) gave rise to easy formation of inclusion bodies [13]. Upon induction with IPTG, both lipase and foldase were expressed in the recombinant E. coli BL21 (DE3) as shown in SDS-PAGE gel (Fig.…”
Section: Cloning and Analysis Of The Genes Of Cs-2 Lipase And Foldasementioning
confidence: 99%
See 1 more Smart Citation
“…To prevent the formation of inclusion bodies, the recombinant cells were cultured at a low temperature (20°C) after the addition of IPTG, for a higher temperature (e.g., 37°C) gave rise to easy formation of inclusion bodies [13]. Upon induction with IPTG, both lipase and foldase were expressed in the recombinant E. coli BL21 (DE3) as shown in SDS-PAGE gel (Fig.…”
Section: Cloning and Analysis Of The Genes Of Cs-2 Lipase And Foldasementioning
confidence: 99%
“…Furthermore, owing to the pathogenicity of strains and/or the requirement of higher lipase productivity, some lipase genes of these strains were expressed in heterogeneous host [11][12][13][14][15]. However, most of these lipases were overexpressed in the bacterial cytoplasm as inactive inclusion bodies.…”
mentioning
confidence: 99%
“…The lipS gene was cloned using primers based on the non-coding region sequences surrounding the P. fluorescens Pf0-1 lipase gene (UniProt ID Q3KIU1). LipS showed high sequence similarity to organic solvent-tolerant lipase rPFL from Pseudomonas fluorescens JCM5963 13) (80% sequence identity) and to Lip9 from Pseudomonas aeruginosa LST-03 14,15) (44% sequence identity). We found that LipS is an alkaline lipase that demonstrates more than 80% of its activity at pH 8-10.5, is tolerant of organic solvents, and has relatively high thermal stability.…”
mentioning
confidence: 99%
“…Figure 6 indicated that 25 °C was the best induction temperature for the expression of functional lipase. Generally speaking, the recombinant cells were cultured at a low temperature after the addition of IPTG to prevent the formation of inclusion bodies [14]. The study by Madan et al indicated 25 °C is beneficial for lipase expression as compare with 30 °C and 37 °C [15].…”
Section: Discussionmentioning
confidence: 99%